2016
DOI: 10.1108/amhid-05-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-focussed cognitive-behaviour therapy for people with mild intellectual disabilities: outcomes of a pilot study

Abstract: Purpose Trauma-focussed cognitive-behaviour therapy (TF-CBT) is the most effective treatment for post-traumatic stress disorder (PTSD). Individuals who present with complex PTSD are among the most complex and challenging patients seen by intellectual disability psychology and psychiatry services. The purpose of this paper is to study TF-CBT intervention for people with intellectual disabilities and complex PTSD. Design/methodology/approach Three groups of adults with intellectual disabilities (ID) presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Four of the papers investigated the experiences of parents with intellectual disabilities (Baum & Burns, ; Gould & Dodd, ; Shewan et al, ; Wilson et al, ). Seven of the studies explored the experience of receiving psychological therapy (Anslow, ; Lewis et al, ; MacDonald et al, ; MacMahon et al, ; Merriman & Beail, ; Roscoe et al, ; Stenfert Kroese et al, ). Three studies looked at the experiences of people with intellectual disabilities as inpatients in hospital (Brown & Beail, ; Clarkson et al, ; Cookson & Dickson, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of the papers investigated the experiences of parents with intellectual disabilities (Baum & Burns, ; Gould & Dodd, ; Shewan et al, ; Wilson et al, ). Seven of the studies explored the experience of receiving psychological therapy (Anslow, ; Lewis et al, ; MacDonald et al, ; MacMahon et al, ; Merriman & Beail, ; Roscoe et al, ; Stenfert Kroese et al, ). Three studies looked at the experiences of people with intellectual disabilities as inpatients in hospital (Brown & Beail, ; Clarkson et al, ; Cookson & Dickson, ).…”
Section: Resultsmentioning
confidence: 99%
“…A stronger indicator is time taken to step aside from the main narrative and explore cases where a single participant might strongly exemplify—or contradict—a thematic point. Some of the better papers also provided evidence of triangulation, audit and credibility checks (e.g., Stenfert Kroese et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the clear need for evidence regarding how to support this population, intervention‐based studies—particularly after the event, and examining abuse of a sexual nature—are lacking (Jones et al, ). Cognitive behavioural therapy (including trauma‐focused variations, i.e., TF‐CBT; see Stenfert Kroese et al, ), eye movement desensitisation and reprocessing (EMDR), exposure therapy and psychodynamic therapy are routinely used in the general population (Jonas et al, ; Schaffner Wilen, ). Indeed, a series of case studies have indicated the effectiveness and acceptability of EMDR in intellectual disability populations (Jowett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study by Stenfert Kroese et al () showed that PTSD in the context of intellectual disability is responsive to TF‐CBT, and further, that participants found the intervention to be acceptable. Only a handful of qualitative studies have reported on responsive interventions where people presented with a clinical need regarding a history of SA specifically (Monahan & Lurie, ; Peckham, Howlett, & Corbett, ; Stenfert Kroese & Thomas, ).…”
Section: Introductionmentioning
confidence: 99%